Effects of phenolic compounds from lingonberry and crowberry on TRPA1 ion channel - Piippo, Iiro (2024)
Transient receptor potential ankyrin 1 (TRPA1) is a non-selective ion channel that has a role in nociception, chemosensation and thermosensation. TRPA1 channel mediates pain, cough, itch and neurogenic inflammation and has been shown to affect the regulation of multiple organ systems. It is mainly expressed in sensory neurons, but also found in other cell types such as epithelial cells and immune cells. TRPA1 channel is activated by a wide range of stimuli. These include noxious exogenous and endogenous chemical stimuli, cold and mechanical stimuli. TRPA1 antagonists are under development for the treatment of pain, cough, inflammation and other TRPA1-associated disorders. Phenolic compounds are a structurally diverse group of compounds that share the phenolic structure where one or multiple hydroxyl groups attach to aromatic ring. These compounds occur naturally in plants, many of which are a part of the normal human diet. Phenolic compounds are secondary metabolites in plants and are associated with defence against plant pathogens and environmental stress such as ultraviolet radiation. Natural phenolic compounds have also been found to have antioxidant, antimicrobial and anti-inflammatory effects. Berries are a rich source of phenolic compounds, and their composition is unique with high amounts of anthocyanins and other flavonoids, phenolic acids and polymeric tannins. This study focused on the phenolic compounds found in two arctic berries, namely lingonberry (Vaccinium vitis-idaea L.) and crowberry (Empetrum nigrum ssp. hermaphroditum), and their effects were investigated on the activity of the TRPA1 ion channel. TRPA1 activity was investigated by measuring TRPA1-dependent changes in the intracellular calcium concentrations by fluo-3-acetoxymethyl ester (Fluo-3-AM) assay in A549 cells. The assay is based on the change in the fluorescence of the Fluo-3-AM molecule when it binds to calcium ion. A549 human lung epithelial cells were selected for the experiments based on earlier findings in the research group ...